2005
DOI: 10.1017/s1365100505040137
|View full text |Cite
|
Sign up to set email alerts
|

E-Stability Does Not Imply Learnability

Abstract: Abstract. The concept of E-stability is widely used as a learnability criterion in studies of macroeconomic dynamics with adaptive learning. In this paper, it is demonstrated, via a counterexample, that E-stability does not in general imply learnability of rational expectations equilibria. The result indicates that E-stability may not a robust device for equilibrium selection.JEL Classification: D83, C62 Keywords: Adaptive learning, E-stability, learnability of REE Introduction and BackgroundIn recent years, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In models with dependence on expectations of future values of the endogenous variables, the correspondence between E-stability and convergence of SG learning no longer holds (see Barucci and Landi, 1997;Heinemann, 2000). Giannitsarou (2005) provides an economic example with lagged endogenous variables in which E-stability of the fundamental REE does not imply convergence of SG learning. 4 It would be possible to extend the analysis to models with lagged endogenous variables.…”
Section: Bayesian and Robust Justifications For The Gsg Algorithmmentioning
confidence: 99%
“…In models with dependence on expectations of future values of the endogenous variables, the correspondence between E-stability and convergence of SG learning no longer holds (see Barucci and Landi, 1997;Heinemann, 2000). Giannitsarou (2005) provides an economic example with lagged endogenous variables in which E-stability of the fundamental REE does not imply convergence of SG learning. 4 It would be possible to extend the analysis to models with lagged endogenous variables.…”
Section: Bayesian and Robust Justifications For The Gsg Algorithmmentioning
confidence: 99%
“…Importantly, theoretical analyses of learning convergence have shown that these learning algorithms may lead to different learnability conditions of RE equilibria (Heinemann, 2000;Giannitsarou, 2005). The LS dominance also has been challenged in previous applied studies (see Bullard and Eusepi, 2005;Carceles-Poveda and Giannitsarou, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For a derivation of the matrix see Giannitsarou (2005). REE), there is a positive probability that the estimates f t might not converge tof.…”
mentioning
confidence: 99%